PENGUKURAN, PENILAIAN, TES, DAN NON-TES DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SMA NEGERI 1 BARUMUN - Oktapiani Siregar, oki; Efendi Siregar, Zulham; fatimah, Siti; Syafnan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of measurement, assessment, test, and non-test techniques in Islamic Religious Education (PAI) learning at SMA Negeri 1 Barumun. The study employed a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation involving PAI teachers and students as research subjects. The findings indicate that measurement and assessment activities have been conducted systematically to evaluate students’ cognitive, affective, and psychomotor competencies. Test instruments are implemented through daily tests, mid-semester assessments, final examinations, oral tests, and practical tests. Meanwhile, non-test techniques are applied through observation, attitude assessment, self-assessment, peer assessment, and portfolio evaluation. The use of both test and non-test instruments provides comprehensive information regarding students’ learning achievements and character development. It can be concluded that the implementation of measurement, assessment, test, and non-test techniques in PAI learning at SMA Negeri 1 Barumun has supported the achievement of learning objectives effectively and comprehensively